PEMANFAATAN POTENSI LOKAL MELALUI INOVASI PANGAN CENDOL LELE DURIAN SEBAGAI USAHA PRODUKTIF - Dalman, Dalman; Fakhrurozi, Moh; Warsiyah, Warsiyah; Saputeri, Noorikha Pandayahesti (Universitas Islam Malang, 2024)
Pekon Mulyorejo, located in Pringsewu Regency, Lampung, has great potential in the development of local food-based culinary businesses. Most of the people in this region make a living as farmers and catfish cultivators, but their production is still sold in raw form with relatively low economic value. This community service program aims to increase the added value of local products through food processing innovation by combining cendol, catfish, and durian into unique and high-selling value culinary products. The methods used in this program include production training, technical assistance, and marketing development. The program was carried out for 6 months involving 25 participants consisting of PKK women and MSME actors in Pekon Mulyorejo. The results of the program showed a significant improvement in the participants' food processing skills, the creation of an innovative product